2015
DOI: 10.1055/s-0034-1396151
|View full text |Cite
|
Sign up to set email alerts
|

Icetexane Diterpenoids from Perovskia atriplicifolia

Abstract: Five new icetexane diterpenoids, namely, perovskatones B-D (1, 3, 4), 1α-hydroxybrussonol (2), and 1α-hydroxypisiferanol (5), were isolated from Perovskia atriplicifolia, together with a new natural product (6) and two known compounds, przewalskin E (7) and brussonol (8). The structures of the new compounds were elucidated by detailed analyses of their MS, IR, 1D, and 2D NMR data. Compounds 1-8 were assayed for their inhibitory hepatitis B virus activities in the HepG 2.2.15 cell line. The results suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Our previous investigation suggested that the petroleum ether extract of P . atriplicifolia showed anti‐HBV (Hepatitis B virus) activity and some bioactive chemicals had been isolated from the petroleum ether extract . But the BuOH extract showed no anti‐HBV activity during the preceding investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous investigation suggested that the petroleum ether extract of P . atriplicifolia showed anti‐HBV (Hepatitis B virus) activity and some bioactive chemicals had been isolated from the petroleum ether extract . But the BuOH extract showed no anti‐HBV activity during the preceding investigation.…”
Section: Introductionmentioning
confidence: 99%
“…274 1α-hydroxybrussonol, a diterpinoid from Perovskia atriplicifolia suppressed the replication of hepatitis B virus DNA with selectivity index of 137.7. 275 The anti-influenza virus activity of six stilbenoids from Gnetum pendulum showed that isorhapontigenin, gnetupendin B, shegansu B, and gnetin D had significant antiinfluenza virus activity in MDCK cells, with IC50 values ranging from 0.67 to 11.99 μg/mL when compared to the positive controls oseltamivir and ribavirin with IC50 values of 0.040 and 5.54 μg/mL, respectively. 276 Tellimagrandin I, a tannin from Cornus canadensis was found effective against herpes simplex virus type 1 (HSV-1) with an EC50 of 2.6 μM for the direct mode and 5.0 μM for the absorption mode of the plaque reduction assay.…”
Section: Othersmentioning
confidence: 99%
“…277 There are several literatures documenting antiviral agents from other natural sources such as those from mushrooms, 278,279 and from marine natural products. [275][276][277][278][279][280][281][282][283]…”
Section: Othersmentioning
confidence: 99%
“…[ 1 2 3 ] Other compounds present in different parts of this plant include other phenolic acids, lignans, flavonoids, and di- and triterpenoids. [ 2 4 5 6 7 8 9 ] P. atriplicifolia is used as folk medicine to treat a variety of ailments, including diabetes. [ 10 11 12 ] However, the anecdotic information on the antidiabetic use of Perovskia sp.…”
Section: Introductionmentioning
confidence: 99%